Ketimpangan Sosial dan Kemiskinan Pada Masyarakat Perkotaan - Muh. Watif; Aulya Ramadhani.JT; Jumiati; Luthfiyah Syam Almazini Tahir; Nurul Hikmah (CV. Ulil Albab Corp, 2024)
The aim of this research is to investigate the factors causing social inequality and poverty in urban communities and identify effective coping strategies. The research method used is a qualitative literature study approach, where data is collected through searching and analyzing various literature sources relevant to the research topic. The results of the analysis show that social inequality and poverty in urban communities are influenced by various factors such as uneven economic growth, limited access to basic services, housing problems, and differences in access to education and health. The impacts of this inequality include health problems, low education, social instability, and deep economic disparities. To overcome social inequality and poverty in urban communities, a holistic response strategy is needed, including investment in inclusive education, strengthening basic infrastructure, community economic empowerment, and affordable housing policies. Collaboration between various stakeholders is also key in creating a more inclusive and sustainable urban society.